2022
DOI: 10.3390/children9060872
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Adherence, Body Mass Index and Emotional Intelligence in Primary Education Students—An Explanatory Model as a Function of Weekly Physical Activity

Abstract: Adolescence is a key developmental period from a health, physical and psychological perspective. In view of this, the present research aimed to establish the relationship between emotional intelligence, Mediterranean diet adherence, BMI and age. In order to address this aim, (a) an explanatory model is developed of emotional intelligence and its relationship with Mediterranean diet adherence, BMI and age, and (b) the proposed structural model is examined via multi-group analysis as a function of whether studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
0
24
1
Order By: Relevance
“…Positive relationships have also been found between physical activity and emotional intelligence. In view of these findings, the study by Melguizo-Ibáñez et al [ 38 ] and López-Sánchez et al [ 39 ] affirm that regular physical exercise promotes the secretion of neurotransmitters, which help to channel disruptive states. Furthermore, Duclos-Bastías et al [ 40 ] state that physical exercise helps to improve young women’s self-image, reporting benefits in self-concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive relationships have also been found between physical activity and emotional intelligence. In view of these findings, the study by Melguizo-Ibáñez et al [ 38 ] and López-Sánchez et al [ 39 ] affirm that regular physical exercise promotes the secretion of neurotransmitters, which help to channel disruptive states. Furthermore, Duclos-Bastías et al [ 40 ] state that physical exercise helps to improve young women’s self-image, reporting benefits in self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…Trigueros et al [ 37 ] state that the subject of physical education helps the physical and healthy development of the adolescent population. Likewise, Melguizo-Ibáñez et al [ 38 ] together with Villodres et al [ 10 ] establish that the socioeconomic level of families also influences young people’s active and healthy lifestyles, with parents being a fundamental element in promoting these lifestyles. Positive relationships have also been found between physical activity and emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument was also used to determine whether the participants were physically active (Do you do more than 3 h of physical activity per week? ), offering a dichotomous response (yes/no) [ 21 , 22 , 23 ]. It was also used to collect the number of hours of study per day (How many hours do you study per day?).…”
Section: Methodsmentioning
confidence: 99%
“…In adolescence, it has been shown that there is a decrease in the amount of time spent doing physical activity as young people move towards more sedentary activities [ 20 ]. Regular physical exercise has been shown to have numerous physical and mental health benefits, including improvements in blood pressure, as well as numerous bone, cognitive, and social benefits [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%